Potensi Wisata Pantai Glagah sebagai Destinasi Wisata Olahraga di Kabupaten Kulon Progo Yogyakarta - Supriyanto, Slamet (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Glagah beach tourism potential as a sports tourism destination in Kulon Progo District Yogyakarta. As an effort to maximize the tourism potential of Glagah Kulon Progo Beach, Yogyakarta Special Region is a sports tourism destination. The research method used qualitative methods, namely data collected from research including, observation, documentation then analyzed descriptively and literature review from various sources. The importance of structuring, managing tourist areas supported by tourism facilities and infrastructure supported by reliable human resources and optimizing the participation of the private sector or the public plus increased investment is an important factor in managing tourist attractions. Â